1973
DOI: 10.1111/j.1432-1033.1973.tb02704.x
|View full text |Cite
|
Sign up to set email alerts
|

Binding of Putrescine and Spermidine to Ribosomes from Escherichia coli

Abstract: 1. The binding of putrescine and spermidine to free 70-S ribosomes has been studied by equilibrium dialysis a t 4" C in the presence of physiological concentrations of K+ and Mg2+. The number of binding sites for each polyamine is approximately 800, and the association constants for putrescine and spermidine are 80 and 500 mM-l, respectively. I n the case of spermidine there is evidence that a small fraction of the sites (3-50/, of the total) have an affinity for spermidine that is about 10 times higher.2. Com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

1975
1975
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…We have shown that the presence of spermidine is crucial for maintaining the correct folding of the helix (h44) of 16S rRNA near the decoding center ( Figure 2 ). Spermidine is a polyamine known to stabilize the folding of RNA molecules including rRNA ( Cohen and Lichtenstein, 1960 ; Weiss and Morris, 1970 ; Cohen, 1971 ; Hardy and Turnock, 1971 ; Turnock and Birch, 1973 ). The upper part of h44 was found as one of the preferred sites for the binding of polyamines ( Amarantos et al, 2002 ) and was particularly observed in the 70S crystal structure from E. coli ( Noeske et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We have shown that the presence of spermidine is crucial for maintaining the correct folding of the helix (h44) of 16S rRNA near the decoding center ( Figure 2 ). Spermidine is a polyamine known to stabilize the folding of RNA molecules including rRNA ( Cohen and Lichtenstein, 1960 ; Weiss and Morris, 1970 ; Cohen, 1971 ; Hardy and Turnock, 1971 ; Turnock and Birch, 1973 ). The upper part of h44 was found as one of the preferred sites for the binding of polyamines ( Amarantos et al, 2002 ) and was particularly observed in the 70S crystal structure from E. coli ( Noeske et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…Recent study has shown the importance of magnesium ions on structure stability of the 30 S from E. coli ( Jahagirdar et al, 2020 ). Moreover, numerous studies have led to the conclusion that polyamines, which are present in all types of cells, can stabilize the structure of the ribosome ( Zillig et al, 1959 ; Cohen and Lichtenstein, 1960 ; Stevens, 1969 ; Weiss and Morris, 1970 ; Cohen, 1971 ; Hardy and Turnock, 1971 ; Turnock and Birch, 1973 ). It was shown that E. coli cells grown in the absence of polyamines contained a large portion of defective 30 S particles ( Echandi and Algranati, 1975 ).…”
Section: Introductionmentioning
confidence: 99%
“…The resulting wild-type subunits were found to have a normal complement of ribosomal proteins and rRNAs (see below) but proved to require higher concentrations of Mg2+ ions in order to reassociate and to give rise to ribosomal monomers particularly sensitive to the hydrostatic pressure induced by centrifugation (see Results). Since polyamines are known to counteract the hydrostatic-pressure-induced dissociation of ribosomes [34], our finding can be explained by the efficient removal of ribosome-bound polyamines caused by the dialysis and the centrifugation in high-salt buffer [35].…”
Section: General Preparationsmentioning
confidence: 99%
“…The ribosomal binding of erythromycin and the peptidyltransferase activity of the 50S subunit are also inhibited (Teraoka and Tanaka, 1973). The 70S ribosomes have been estimated to contain about 800 binding sites for each polyamine, although the binding affinities for the three polyamines are greatly different (Stevens, 1969;Turnock and Birch, 1973). In addition, it is known that the polyamines interact with the rRNA moiety of ribosomes (Turnock and Birch, 1973).…”
Section: Resultsmentioning
confidence: 99%